2007
DOI: 10.1111/j.1530-0277.2007.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone and Cognitive Behavioral Coping Skills Therapy for the Treatment of Alcohol Drinking and Eating Disorder Features in Alcohol‐Dependent Women: A Randomized Controlled Trial

Abstract: When used in conjunction with CBCST, naltrexone did not significantly improve drinking outcomes in the overall sample of alcohol-dependent women. However, naltrexone may be of benefit to women who are unable to maintain total abstinence from alcohol. For women with concurrent eating pathology, participation in treatment for alcoholism may be associated with improvements in eating pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 62 publications
2
59
0
4
Order By: Relevance
“…Inhibition of relapse for a prolonged period of time following extinction, as observed in this study, might provide a significant window of opportunity during which additional therapeutic interventions could be introduced to further forestall relapse. For example, stress is a major determinant of relapse (Sinha, 2009) and cognitive behavioral therapies that help to develop coping skills have been effective in treating alcohol abuse (O'Malley et al, 2007). As evidenced by the eventual return to baseline levels of responding toward the end of the reacquisition phase of our study, pharmacologically augmented exposure therapy might be most beneficial if implemented as a recurring treatment strategy for the management of cocaine dependence.…”
Section: Discussionmentioning
confidence: 88%
“…Inhibition of relapse for a prolonged period of time following extinction, as observed in this study, might provide a significant window of opportunity during which additional therapeutic interventions could be introduced to further forestall relapse. For example, stress is a major determinant of relapse (Sinha, 2009) and cognitive behavioral therapies that help to develop coping skills have been effective in treating alcohol abuse (O'Malley et al, 2007). As evidenced by the eventual return to baseline levels of responding toward the end of the reacquisition phase of our study, pharmacologically augmented exposure therapy might be most beneficial if implemented as a recurring treatment strategy for the management of cocaine dependence.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the majority of the studies evaluated by the meta-analysis did not report the results obtained by female patients in detail, while the few studies in which this information was reported found contrasting results. Namely, the RCT in which only female patients were recruited failed to demonstrate a significant effect of naltrexone [61] . In this RCT, naltrexone did not improve drinking outcomes, although naltrexone delayed the on- set of subsequent drinking days among women who lapsed.…”
Section: Resultsmentioning
confidence: 99%
“…Sin embargo, un análisis posterior ha comprobado que entre las mujeres que bebieron durante el tratamiento, las que tomaban naltrexona presentaron un mayor número de días entre el primer consumo y los siguientes días de consumo de alcohol, que las que tomaron placebo 65 .…”
Section: Predictors Of Response To Treatment With Naltrexoneunclassified
“…However another study has shown that among women who drank during the treatment, those who took naltrexone, showed a higher number of days between the first and the next drinking days, in comparison with those who took placebo 65 . Baros, Latham and Anton 66 have proposed that gender differences can be more related to sample size or outcome variables than to pharmacological or biological differences in the response to naltrexone.…”
Section: Predictors Of Response To Treatment With Naltrexonementioning
confidence: 99%